2005
DOI: 10.1007/s10751-005-9148-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Ion Irradiated Ferromagnetic Films: The Cases of Cobalt and Iron

Abstract: Polycrystalline, e-gun deposited Co, Fe and Co/Fe films, tens of nanometers thick, have been irradiated with Ne, Kr, Xe and/or Fe ions to fluences of up to 5 Â 10 16 ions/cm 2 . Changes in the magnetic texture induced by the implanted ions have been measured by means of hyperfine methods, such as Magnetic Orientation Mössbauer Spectroscopy (Fe), and by Magneto-Optical Kerr Effect and Vibrating Sample Magnetometry. In Co and CoFe an hcp Y fcc phase transition has been observed under the influence of Xe-ion impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
1
1
Order By: Relevance
“…However, in these studies no changes in the magnetization were reported. This is attributed either to the existence of implantation effects [13,14], which is not the case in the current work, or the use of much lower fluences (two orders of magnitude lower) [11,12] than in the current work.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…However, in these studies no changes in the magnetization were reported. This is attributed either to the existence of implantation effects [13,14], which is not the case in the current work, or the use of much lower fluences (two orders of magnitude lower) [11,12] than in the current work.…”
contrasting
confidence: 67%
“…In the literature, changes in the structural and magnetic properties of iron films induced by heavy ion irradiation and/or implantation are reported [11][12][13][14]. However, in these studies no changes in the magnetization were reported.…”
mentioning
confidence: 99%
“…A similar process is observed by the authors of [3] in Fe/Si films. Also, do not rule out the possibility of partial amorphization of the film and phase transitions that can be caused by ion irradiation [4][5]. Future studies by means of transmission electron microscopy and X-ray diffraction analysis will clarify the nature of changes in the structure of cobalt films under the influence of Ga+ ions.…”
Section: Resultsmentioning
confidence: 94%